2017
DOI: 10.1007/s12194-017-0423-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between tumor volume and quantitative values calculated using two-dimensional bone scan images

Abstract: The bone scan index (BSI) is calculated from a whole-body bone scan image; it shows the tumor burden in bone as a percentage of total skeletal mass. It has been used to determine the prognosis and to assess treatment effects; however, little has been reported on whether the BSI calculated using a two-dimensional image can accurately evaluate the three-dimensional spread in tumor volume. We investigated the relationship between tumor volume and BSI using Monte Carlo simulation (MCS). We simulated a gamma camera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…We have investigated that BONENAVI ® often resulted in false-positive or false-negative in patients with small tumor burden (e.g., EOD = 1 and low activity) [ 24 ]. Others have also reported that BSI was strongly influenced by tumor location, volume, and scan uptake time in a simulation study [ 25 ] and clinical setting [ 26 ]. It could be due to attenuation by scatters and different activity of osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…We have investigated that BONENAVI ® often resulted in false-positive or false-negative in patients with small tumor burden (e.g., EOD = 1 and low activity) [ 24 ]. Others have also reported that BSI was strongly influenced by tumor location, volume, and scan uptake time in a simulation study [ 25 ] and clinical setting [ 26 ]. It could be due to attenuation by scatters and different activity of osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…When conducting research at multiple facilities, it is necessary to pay attention to changes in the quality of the input image. For example, the quality of CT images directly contributes to the accuracy of diagnostic ability as a fused image with SPECT as well as the evaluation of CT alone [9][10][11]20]. Although the CT image of our protocol had a low dose, we were able to evaluate the lesion by ensuring sufficient image quality in the diagnosis of bone lesions.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some challenges in whole-body planar analysis. For instance, information in the front-back direction is compressed 2D information, which renders the evaluation with the accumulation pattern insufficient (light accumulation) [8], with low accuracy of the area affected by overlap [9]. Recent years have witnessed an upsurge in the number of facilities that have added single-photon emission computed tomography/computed tomography (SPECT/CT), three-dimensional (3D) imaging, to whole-body planar scintigraphy.…”
Section: Introductionmentioning
confidence: 99%
“…The volume of bone marrow metastases was calculated incorporating related approaches form other imaging methods. 40 , 41 , 42 First, a reference was created for the total volume of bone marrow present in children in general using magnetic resonance data of three representative patients of different age (3 months, 1 year, 4 years). Then, patients' MIBG scintigraphy scans were evaluated for their MIBG‐distribution in bone marrow, and the distribution was set in correlation to the established reference to calculate the metastatic volume affecting the total bone marrow.…”
Section: Methodsmentioning
confidence: 99%
“…The volume of bone marrow metastases was added. The volume of bone marrow metastases was calculated incorporating related approaches form other imaging methods 40–42 . First, a reference was created for the total volume of bone marrow present in children in general using magnetic resonance data of three representative patients of different age (3 months, 1 year, 4 years).…”
Section: Methodsmentioning
confidence: 99%